2022
DOI: 10.3389/fpls.2022.1045225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pythium oligandrum on improvement of lucerne yield, root development and disease score under field conditions

Abstract: IntroductionBiological control of root diseases of lucerne (Medicago sativa L.) has potential benefits for stand performance but this remains unsupported by evidence from practical field studies.MethodsIn field experiments at three sites our objectives were to determine the effect of Pythium oligandrum, as spring, autumn and intensive regime treatments on (i) lucerne plant density and root traits development, and (ii) forage yield and forage traits. Lucerne stands were managed under two or three treatments: no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…A similar conclusion was reported by Bradford et al [72], who found a relationship between the mean time of the germination of pepper seeds and the emergence in primed vs. control treatments. Field experiments also enabled the evaluation of root morphology development, as tap-root diameter and lateral root number formation have clear connections with stand productivity and root disease resistance [53,73]. In this regard, the consistent improvement of root branching under potassium permanganate priming can be highlighted.…”
Section: Relationships Of Simple Laboratory Tests To Field Condition ...mentioning
confidence: 96%
“…A similar conclusion was reported by Bradford et al [72], who found a relationship between the mean time of the germination of pepper seeds and the emergence in primed vs. control treatments. Field experiments also enabled the evaluation of root morphology development, as tap-root diameter and lateral root number formation have clear connections with stand productivity and root disease resistance [53,73]. In this regard, the consistent improvement of root branching under potassium permanganate priming can be highlighted.…”
Section: Relationships Of Simple Laboratory Tests To Field Condition ...mentioning
confidence: 96%